Adjunctive application of solid‐state culture products and its freeze‐dried powder from Aspergillus sojae for semi‐hard cheese. (24th June 2020) - Chintagavongse, Napaporn; Yoneda, Tomoki; Ming‐Hsuan, Chi; Hayakawa, Toru; Wakamatsu, Jun‐ichi; Tamano, Koichi; Kumura, Haruto
Abstract: BACKGROUND: Species belonging to the genus Aspergillus have been used in traditional Japanese fermented foods. Aspergillus sojae is a species responsible for strong proteolytic activity. Freeze‐drying treatments followed by physical disruption enables the pulverization of the mycelia of A. sojae RIB 1045 grown in whey protein‐base solid media. Intracellular proteases were extracted using this protocol to compare extracellular protease activity in terms of the reaction's pH dependence in the presence or absence of inhibitors. RESULT: With different sensitivities to inhibitors, intracellular and extracellular proteases showed the strongest activity under acidic conditions, which were considered suitable for cheese application. The raw culture product (CP) and its freeze‐dried product (FDP) were mixed with cheese curds, prepared according to Gouda‐type cheese‐making methods, and were allowed to ripen for 3 months. Chemical analysis of the products showed 13.3% water‐soluble nitrogen (WSN) in the control, which had received noncultured media, whereas 20.0% and 21.1% WSN was found in the CP and FDP experimental cheeses, respectively. Although these adjuncts significantly increased WSN, an insignificant difference was found between CP and FDP. Free fatty acids in all experimental cheeses were similar, showing that CP and FDP caused no rancid defects. CONCLUSION: The introduction of freeze‐drying treatments accompanied by cell disruption resulted in a negligible effect in terms of WSN. However, the application of A. sojae can be beneficial when it comes to increasing the level of WSN compared with A. oryzae, as shown in our previous study. © 2020 Society of Chemical Industry